Self-Learning Activity Package Promoting Life Skills in Communication Arts Careers for Undergraduate Students at Suan Dusit University - Sangwichien, Suttama; Chongchaikit, Maturos (Journal of Multidisciplinary in Social Sciences, 2023)
This research had the objectives to (1) determine the essential life skills for communication arts careers; (2) develop the self-learning activity package promoting life skills for communication arts careers; (3) study the usage results of the self-learning activity package. The sample used in this research were 24 lecturers and 40 students in Communication Arts Program at Suan Dusit University. The research tools were google form and website for used distributing the whole set of activities and research tools for experts and students, questionnaire of essential life skills for the instructors’opinion, assessment form and questionnaire for the experts’opinion, self-assessment after trying the activity package for students, and satisfaction questionnaire for students. The data were analyzed, using frequency, percentage, S.D. and descriptive writing. The research results showed that (1) The essential life skills determined for communication arts careers were the 3 sets of activity package consist; communication skill, interpersonal relationship skill and making contribution, and critical thinking skill and making decision, consisting of 11 competences, 31 indicators, 10 units and 13 activity plans with, in total, 35 group and individual activities, including the self-tests for during and after the usage of activity package; (2) the evaluation results of the experts was at the highest level, both for the consistency of the activity sets with the life skills and the website design; (3) the usage result of the activity sets demonstrated the ability of students to fully work, with the results of passing the 60% criteria in the second round, which were 72.5% (29 people), 77.5% (31 people) and 57.5% (23 people) for sets 1-3, respectively; (4) the students were satisfied with the content - utility and presentation style at the moderate level, respectively at 3.41 and 3.25.